La contribución de las refugiadas colombianas a la Agenda Global de Desarrollo a través de su empoderamiento en la acción colectiva para la defensa de los derechos - Elena MUT-MONTALVA (Revista Iberoamericana de Estudios de Desarrollo)
The purpose of this study is to delve into the contributions and meanings of social and political activism in defense of human rights carried out by Colombian refugees living in Spain and their close relationship with relevant two processes that they experience: of empowerment and generation of new identities. Colombian refugees in Spain are an example of resilience that is based on the creation of networks of activism in defense of human rights of exiled women. They have emerged as social agents with the capacity for interlocution to claim rights in the different territories in which they experience their transnational existence within the framework of the Global Development Agenda. This participation is crystallized through social awareness activities, education for the construction of a critical global citizenship and international political advocacy through which they spread their principles and values to promote social change towards more inclusive and egalitarian societies.